Physical and Chemical Analysis of Anchovy Nuggets with Additional Moringa and Cassava Leaves to Prevent Stunting - Windi Habsari; Dita Ayu Lestari; Willcent Twinatmaja Hartanto (The University of Lampung, 2025)
Supplementation of moringa and cassava leaves in anchovy nuggets has can improve nutrition value. The aim of this study was to evaluate the effect of moringa and cassava leaves in enriching nutrition of anchovy nugget. The experiment was performed with five compositions (anchovy:moringa leaves:cassava leaves), namely F0 (100:0:0), F1 (96:2:2), F2 (92:4:4), F3 (88:6:6) and F4 (84:8:8). The physical parameters included color analysis and organoleptic test using 5 points hedonic test involved 25 panelist. Nutritional content was determined through proximate analysis. Results show that addition of moringa and cassava leaves decreased the color of anchovy nuggets, except the yellowness which was significantly increased in F3 treatment. The highest protein content was obtained from F4 formulation, the highest carbohydrate content was given by F3 and F4 treatments, and the lowest fat content was provided by nuggets from F3 and F4. The highest organoleptic score was F0 for taste, F2 and F3 for flavor, F3 for color, and F3 and F4 for overall scores. The supplementation of leaves generate unpleasant flavor. The addition of 6 g moringa and cassava leaves improve nutritional value of anchovy nuggets with acceptable sensory attributes that can be employed to solve stunting problem. Keywords: Anchovy nugget, Cassava leaf, Moringa leaf, Physico–chemical, Stunting.